TRENDS IN THE CHANGES OF CONSUMER NUTRITIONAL NEEDS IN POLAND IN THE YEARS 2003–2015 - Szwacka-Mokrzycka, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2018)
The article presents main trends in the changes of nutritional needs in Poland over the past dozen years. Main goal of the article is to determine the direction and scope of the changes in consumption patterns of Poles in progress in the first and second decade of the 21st century. Starting point of the analysis consists in presenting the methods for studying the pace of development of food consumption and the changes of its structure. Next, the prioritization of nutritional needs was presented basing on the analysis and assessment of average income elasticity factors for consumption for the years 2003–2015. The conducted analysis of the shaping of nutritional needs of Polish households reflects the growing level of satisfaction of the needs as well as quality changes, together with substitution processes within the analysed food groups.